Case Report: A Spinal Ischemic Lesion in a 24-Year-Old Patient With Fabry Disease - Krämer, Julia; Glaser, Felix; Hasselblatt, Martin; Brand, Eva; Pogoda, Christian; Lenders, Malte; Wiendl, Heinz; Meuth, Sven G.; Duning, Thomas (Frontiers in Immunology, 2020)
Background: While cerebral lesions are common in Fabry disease (FD), spinal lesions have not been described, and their presence was suggested to be indicative of multiple sclerosis. Here, we present a FD patient with histopathological confirmed spinal ischemic stroke. Case presentation: A patient with genetically and biochemically diagnosed FD and characteristic manifestations (acroparesthesia, angiokeratomas, hypohidrosis, microalbuminuria, myocardial hypertrophy) presented with paraplegia, loss of all sensory modalities below Th9, and loss of bowel and bladder function. While cranial MRI was inconspicuous, spinal MRI showed a T2 hyperintense, non-contrast-enhancing lesion of the thoracic spinal cord. Lumbar puncture revealed mild pleocytosis, increased total protein and lactate levels, decreased glucose ratio, and negative oligoclonal bands. Rheumatic, neoplastic, and infectious disorders were excluded. The patient received intravenous and intrathecal methylprednisolone, plasmapheresis, intravenous immunoglobulins, and cyclophosphamide without clinical improvement. A biopsy of the thoracic lesion was performed. A histopathological examination revealed necrotic tissue consistent with spinal cord ischemia. Diagnostic work-up for stroke etiology clarification was not conspicuous. Two years onward, the patient suffered from a pontine infarction and a transient ischemic attack. Conclusion: The current case highlights the possible occurrence of spinal ischemic lesions in FD. Thus, the diagnosis of FD should not be prematurely discarded in the presence of spinal lesions.